Simplify the expression $(3k^4)^4$

Question image

Understand the Problem

The question asks us to simplify the expression. To do this, we will do the following: first, distribute the exponent and then simplify.

Answer

$81k^{16}$
Answer for screen readers

$81k^{16}$

Steps to Solve

  1. Distribute the exponent

Apply the power of a product rule: $(ab)^n = a^n b^n$ $$(3k^4)^4 = 3^4 \cdot (k^4)^4$$

  1. Simplify $3^4$

Calculate $3^4$: $$3^4 = 3 \cdot 3 \cdot 3 \cdot 3 = 81$$

  1. Simplify $(k^4)^4$

Apply the power of a power rule: $(a^m)^n = a^{m \cdot n}$ $$(k^4)^4 = k^{4 \cdot 4} = k^{16}$$

  1. Combine the terms

Combine the simplified terms: $$3^4 \cdot (k^4)^4 = 81 \cdot k^{16} = 81k^{16}$$

$81k^{16}$

More Information

The power of a product rule and the power of a power rule are crucial for simplifying expressions with exponents.

Tips

A common mistake is forgetting to apply the outer exponent to the coefficient (3 in this case). Remember to apply the exponent to all parts of the term inside the parentheses. Also, a frequent error is adding the exponents when you should multiply them.

AI-generated content may contain errors. Please verify critical information

Thank you for voting!
Use Quizgecko on...
Browser
Browser